Determination of Fenspiride Hydrochloride Residues on Pharmaceutical Manufacturing Equipment Surfaces by HPLC Method - Fedosenko, Ganna; Yegorova, Alla; Scrypynets, Yulia; Leonenko, Inna; Vitukova, Ekaterina (Київський національний університет імені Тараса Шевченка, 2018)
The cleaning procedure must be validated, so special attention must be devoted to the methods used for determination of trace amounts of drugs. A rapid, sensitive, and specific reverse phase high-performance liquid chromatographic (HPLC) method was developed for the quantitative determination of fenspiride hydrochloride residues on pharmaceutical manufacturing equipment surfaces. The calibration curve was linear over a concentration range from 1.0 to 100.0 μg/ml with a correlation coefficient of 0.99994. The detection limit and quantitation limit were 0.41 μg/ml and 1.25 μg/ml, respectively. The developed method was validated with respect to specificity, linearity, limit of detection, accuracy and precision.
Keywords: cleaning validation; fenspiride hydrochloride; residues; swab analysis; HPLC